Analysis and Computational Methodology of Non-Isothermal Kinetics of Bentonite - Kurbonov, Jamshed Madjidovich (International Journal of Intelligent Systems and Applications in Engineering, 2024)
This study presents an experimentally identified derivatogram of bentonite from the Navbahor mine, the texture of bentonite, physical and chemical characteristics, chemical composition, and their analysis of the retaining substance used in the preparation of nanocatalysts based on Zol-gel technology.